Studies on Capture of Modified Ca-Based Sorbents for Zn, Pb, As in Coal During the Process of Combustion Based on the Analysis of Fundamental Characteristics of Trace Elements and Coal Samples - Li, Dongwei; Huang, Tao (Asian Journal of Chemistry, 2014)
This paper systematically expounds the fundamental characteristics of trace elements (zinc, lead, arsenic) in the coal samples, including content, occurrence, phases, microstructure, morphology and melting properties by the analysis of AFS, XRD, SEM-EDX and TG-DSC. It also discusses the thermodynamic behaviour and the mechanisms of migration and transformation on the basis of the experimental phenomena and the analyzed information. The capture efficiencies of the modified Ca-based sorbents (MCS) for Zn, Pb, As were studied comparative to the experimental results of calcium carbonate. The content of Zn, Pb and As in the coal samples were nearly all exceeding the standard values. Zn and Pb occurred mainly in the form of exchangeable, bound-sulfide and residue in the coal samples and more than 50 % of As was bound-sulfide. Zn, Pb and As in the most coal samples evaporated and gasified following the priority of As > Zn > Pb during the process of coal static combustion experiment. The lowest volatilization rate of Zn, Pb and As with the addition of modified Ca-based sorbents were18.81, 14.44 and 26.13 %, respectively under the optimal experimental condition, which were much lower than the ratio with calcium carbonate under the same experimental condition. The surface area, pore diameter and porosity of calcium carbonate modified by Al2(SO4)3 were obviously improved, some g-Al2O3 was found on the surface of the particle and the melting temperature of the coal mixed with modified Ca-based sorbent was high.